Industrial revolution (IR) 4.0 in construction engineering education: a bibliometric analysis - N.S. Zabidin,; S. Belayutham,; C.K.I.C. Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Industrial Revolution 4.0 (IR 4.0) is a high technology digitization to enhance communication networks, organization and management, as well as production and processes across industries. The rate of changes and its convergence towards IR 4.0 would require new talent, knowledge and skills for current and future generations to retain and generate new workforces. As technology in the construction industry is evolving at a fast pace, the current teaching-learning syllabus and pedagogy should transform accordingly to accommodate future job requirements. Due to the rawness of this concept in the construction industry and to its education, this study aims to explore the state of the art as well as the state of practice of IR 4.0 and Education 4.0 from the perspective of construction engineering. Therefore, a systematic review was conducted to analyze the relevant research papers related to IR 4.0 and Education 4.0 within the Scopus database, ranging from year 2011 until present. A bibliometric analysis has been outlined following the Preferred Reporting Items for Systematic Review and Meta- Analyses (PRISMA) statement. Findings from this study would provide a thorough understanding on the past efforts in advancing the construction engineering education aspect, subsequently highlighting gaps to be filled for future endeavors, particularly in equipping the construction engineering education for IR 4.0.